6.183 Problems 18201 to 18300

Table 6.365: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

18201

\[ {}2 x +3 y+1+\left (2 y-3 x +5\right ) y^{\prime } = 0 \]

18202

\[ {}x y^{\prime } = \sqrt {x^{2}+y^{2}} \]

18203

\[ {}y^{2} = \left (x^{3}-x y\right ) y^{\prime } \]

18204

\[ {}x^{2} y^{3}+y = \left (y^{2} x^{3}-x \right ) y^{\prime } \]

18205

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2}-2 y y^{\prime } = 0 \]

18206

\[ {}x y^{\prime }+y = y^{2}+x^{2} y^{\prime } \]

18207

\[ {}x y y^{\prime } = y^{2}+x^{2} y^{\prime } \]

18208

\[ {}\left ({\mathrm e}^{x}-3 x^{2} y^{2}\right ) y^{\prime }+y \,{\mathrm e}^{x} = 2 x y^{3} \]

18209

\[ {}y^{\prime \prime }+2 x {y^{\prime }}^{2} = 0 \]

18210

\[ {}x^{2}+y = x y^{\prime } \]

18211

\[ {}x y^{\prime }+y = x^{2} \cos \left (x \right ) \]

18212

\[ {}6 x +4 y+3+\left (3 x +2 y+2\right ) y^{\prime } = 0 \]

18213

\[ {}\cos \left (x +y\right ) = x \sin \left (x +y\right )+x \sin \left (x +y\right ) y^{\prime } \]

18214

\[ {}x^{2} y^{\prime \prime }+x y^{\prime } = 1 \]

18215

\[ {}y^{2} {\mathrm e}^{x y}+\cos \left (x \right )+\left ({\mathrm e}^{x y}+y \,{\mathrm e}^{x y} x \right ) y^{\prime } = 0 \]

18216

\[ {}y^{\prime } \ln \left (x -y\right ) = 1+\ln \left (x -y\right ) \]

18217

\[ {}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}} \]

18218

\[ {}y^{2}-3 x y-2 x^{2} = \left (x^{2}-x y\right ) y^{\prime } \]

18219

\[ {}\left (x^{2}+1\right ) y^{\prime }+2 x y = 4 x^{3} \]

18220

\[ {}{\mathrm e}^{x} \sin \left (y\right )+{\mathrm e}^{x} \cos \left (y\right ) y^{\prime } = y \sin \left (x y\right )+x \sin \left (x y\right ) y^{\prime } \]

18221

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime } = 0 \]

18222

\[ {}\left (x \,{\mathrm e}^{y}+y-x^{2}\right ) y^{\prime \prime } = 2 x y-{\mathrm e}^{y}-x \]

18223

\[ {}\left (1+x \right ) {\mathrm e}^{x} = \left (x \,{\mathrm e}^{x}-y \,{\mathrm e}^{y}\right ) y^{\prime } \]

18224

\[ {}x^{2} y^{4}+x^{6}-x^{3} y^{3} y^{\prime } = 0 \]

18225

\[ {}y^{\prime } = 1+3 \tan \left (x \right ) y \]

18226

\[ {}y^{\prime } = 1+\frac {y}{x}-\frac {y^{2}}{x^{2}} \]

18227

\[ {}y^{\prime } = \frac {2 x y \,{\mathrm e}^{\frac {x^{2}}{y^{2}}}}{y^{2}+y^{2} {\mathrm e}^{\frac {x^{2}}{y^{2}}}+2 x^{2} {\mathrm e}^{\frac {x^{2}}{y^{2}}}} \]

18228

\[ {}y^{\prime } = \frac {x +2 y+2}{y-2 x} \]

18229

\[ {}3 x^{2} \ln \left (y\right )+\frac {x^{3} y^{\prime }}{y} = 0 \]

18230

\[ {}\frac {3 y^{2}}{x^{2}+3 x}+\left (2 y \ln \left (\frac {5 x}{x +3}\right )+3 \sin \left (y\right )\right ) y^{\prime } = 0 \]

18231

\[ {}\frac {y-x}{\left (x +y\right )^{3}}-\frac {2 x y^{\prime }}{\left (x +y\right )^{3}} = 0 \]

18232

\[ {}x y^{2}+y+x y^{\prime } = 0 \]

18233

\[ {}x^{2} y^{\prime \prime } = y^{\prime } \left (3 x -2 y^{\prime }\right ) \]

18234

\[ {}3 x^{2} y-y^{3}-\left (3 x y^{2}-x^{3}\right ) y^{\prime } = 0 \]

18235

\[ {}x \left (x^{2}+1\right ) y^{\prime }+2 y = \left (x^{2}+1\right )^{3} \]

18236

\[ {}y^{\prime } = \frac {-3 x -2 y-1}{2 x +3 y-1} \]

18237

\[ {}{\mathrm e}^{x^{2} y} \left (1+2 x^{2} y\right )+x^{3} {\mathrm e}^{x^{2} y} y^{\prime } = 0 \]

18238

\[ {}3 x^{2} {\mathrm e}^{y}-2 x +\left (x^{3} {\mathrm e}^{y}-\sin \left (y\right )\right ) y^{\prime } = 0 \]

18239

\[ {}y^{2} y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

18240

\[ {}3 x y+y^{2}+\left (3 x y+x^{2}\right ) y^{\prime } = 0 \]

18241

\[ {}x^{2} y^{\prime } = y^{2}+x y+x^{2} \]

18242

\[ {}x y^{\prime }+y = y^{2} \ln \left (x \right ) \]

18243

\[ {}\frac {\cos \left (y\right )}{x +3}-\left (\sin \left (y\right ) \ln \left (5 x +15\right )-\frac {1}{y}\right ) y^{\prime } = 0 \]

18244

\[ {}x^{2} y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18245

\[ {}x y+y-1+x y^{\prime } = 0 \]

18246

\[ {}x^{2} y^{\prime }-y^{2} = 2 x y \]

18247

\[ {}y^{\prime \prime } = 2 y {y^{\prime }}^{3} \]

18248

\[ {}x^{\prime }+x \cot \left (y \right ) = \sec \left (y \right ) \]

18249

\[ {}x y^{\prime \prime }-y^{\prime } = 3 x^{2} \]

18250

\[ {}x y^{\prime \prime }+y^{\prime } = 0 \]

18251

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 4 x \]

18252

\[ {}x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = 1 \]

18253

\[ {}y^{\prime \prime }-2 y^{\prime } = 6 \]

18254

\[ {}y^{\prime \prime }-2 y = \sin \left (x \right ) \]

18255

\[ {}y^{\prime \prime } = {\mathrm e}^{x} \]

18256

\[ {}y^{\prime \prime }-2 y^{\prime } = 4 \]

18257

\[ {}y^{\prime \prime }-y = \sin \left (x \right ) \]

18258

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

18259

\[ {}y^{\prime \prime }+2 y^{\prime } = 6 \,{\mathrm e}^{x} \]

18260

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }-5 y = 0 \]

18261

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (x^{2}+6\right ) y = 0 \]

18262

\[ {}y^{\prime \prime }-y = 0 \]

18263

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

18264

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

18265

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18266

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

18267

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

18268

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

18269

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18270

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18271

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

18272

\[ {}y^{\prime \prime }+y = 0 \]

18273

\[ {}y^{\prime \prime }-y = 0 \]

18274

\[ {}x y^{\prime \prime }+3 y^{\prime } = 0 \]

18275

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

18276

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

18277

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

18278

\[ {}y^{\prime \prime }-\frac {x y^{\prime }}{x -1}+\frac {y}{x -1} = 0 \]

18279

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

18280

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

18281

\[ {}y^{\prime \prime }-x f \left (x \right ) y^{\prime }+f \left (x \right ) y = 0 \]

18282

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

18283

\[ {}x y^{\prime \prime }-\left (x +n \right ) y^{\prime }+n y = 0 \]

18284

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

18285

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

18286

\[ {}x y^{\prime \prime }-\left (x +3\right ) y^{\prime }+3 y = 0 \]

18287

\[ {}y^{\prime \prime }-f \left (x \right ) y^{\prime }+\left (f \left (x \right )-1\right ) y = 0 \]

18288

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

18289

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

18290

\[ {}y^{\prime \prime }+8 y = 0 \]

18291

\[ {}2 y^{\prime \prime }-4 y^{\prime }+8 y = 0 \]

18292

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18293

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 0 \]

18294

\[ {}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18295

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

18296

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18297

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

18298

\[ {}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0 \]

18299

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18300

\[ {}y^{\prime \prime } = 4 y \]